Nb2O5 hole blocking layer for hysteresis-free perovskite solar cells - Fernandes, Silvia L. [UNESP]; Véron, Anna C.; Neto, Nilton F.A. [UNESP]; Nüesch, Frank A.; Dias da Silva, José H. [UNESP]; Zaghete, Maria A. [UNESP]; Graeff, Carlos F. de O. [UNESP] (Elsevier, 2016)
Perovskite solar cells have attracted attention due its high conversion efficiency and low cost. In this work, Nb2O5 is used as an alternative compact hole blocking layer in conjunction with mesoporous TiO2 and CH3NH3PbI3 in perovskite solar cells. The influence of Nb2O5 layer thickness was studied and it was found to strongly influence the J-V hysteresis of the cells. Devices constructed with 50 nm Nb2O5 have small or undetectable hysteresis, which becomes detectable and increases with increasing Nb2O5 layer thickness. For the best device, energy conversion efficiency of up to 12%, short-circuit currents of 17 mA/cm2 and fill factors of 74% were found. These parameters are comparable to the best performance of similar devices where the compact layer is TiO2. In addition, the use of Nb2O5 improved the stability of the solar cells under illumination. These improvements are attributed to a better extraction of photogenerated electrons in the perovskite layer.
Keywords: Hysteresis; Methyl ammonium lead iodide; Niobium pentoxide; Perovskite solar cells; Stability